The Intersection of Geography, Topography and Mindset: A Nuanced Understanding of Regional, Rural and Remote Students’ Tertiary Participation in Australia - Webb, Susan Christine; Reshmi Lahiri-Roy; Elizabeth Knight; Koshy, Paul (Australian and International Journal of Rural Education, 2024)
This paper explores the notion of rurality in Australian tertiary education as part of an investigation into the subtle but distinct differences in participation thinking and patterns among young people in regional, rural and remote (RRR) communities. Drawing on qualitative data gathered as part of a wider research project for the National Centre for Vocational Education Research, the paper examines whether student participation in tertiary education is shaped by factors more deeply related to a sense of connection to community, the relationality and reflexivity as related to context, as well the proximity to major tertiary education infrastructure, such as campuses. This analysis of place challenges traditional geographical lenses that emphasise RRR location in and of itself. Hence, the paper contributes to a more nuanced understanding of language in relation to RRR location as used in Australian policy, providing insights into the contested nature of the Australian term RRR, the concept of rurality in the wider literature, and concomitantly, investigating the impact of the same on youth participation in Australian tertiary education.